We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
249
4
avatar

Consider the sequence defined by  \(\begin{cases} s_0=0\\ s_1=3\\ s_n=6s_{n-1}-9s_{n-2} & \text{if }n\ge 2 \end{cases}\) 

Find a closed form for \(s_n\).

__________________________________________________________________

Consider the sequence defines by \(\begin{cases} t_0=5\\ t_1=9\\ t_n=6t_{n-1}-9t_{n-2} & \text{if }n\ge 2 \end{cases} \)

Find the closed form for \(t_n\).

__________________________________________________________________

I am struggling to try to solve these problems. Especially the second one. i listed the terms out, but i just cant seem to find the pattern. Help, hints, or the solution would be appreciated!

 Sep 16, 2018
 #1
avatar
+1

1)-

 

 S(0) =0
S(1)=3
S(2)=18
S(3)=81
S(4)=324
S(5)=1215
S(6)=4374
S(7)=15309
0, 3, 18, 81, 324, 1215, 4374, 15309, 52488, 177147, 590490, 1948617, 6377292, 20726199, ...etc.
a_n = 3^(n - 1) (n - 1)  - The closed form.

 

2)-

 

t(0)=5
t(1)=9
t(2)=9
t(3)=-27
t(4)=-243
t(5)=-1215
t(6)=-5103
t(7)=-19683
5, 9, 9, -27, -243, -1215, -5103, -19683, -72171, -255879, -885735, -3011499....etc.
a_n = -3^(n - 1) (2 n - 7) - The closed form.

 Sep 16, 2018
 #2
avatar+27775 
+1

I get these to be:

 

sn = n3n   and tn = (5 - 2n)3n  where n starts from 0.  (i.e. n = 0, 1, 2, 3, ...)

 Sep 16, 2018
 #3
avatar
+1

1- Expand the following:
3^(n - 1) (n - 1) = n×3^n

Express 3^(n - 1) (n - 1) as a difference of fractions.
3^(n - 1) (n - 1) = 3^(n - 1) n - 3^(n - 1):
3^(n - 1) n - 3^(n - 1) = n*3^n

 

2- Expand the following:
-3^(n - 1) (2 n - 7) = 3^n (5 - 2 n)

Express -3^(n - 1) (2 n - 7) as a difference of fractions.
-3^(n - 1) (2 n - 7) = -(3^(n - 1) (-7)) - 3^(n - 1)×2 n:
-(-7×3^(n - 1)) - 2×3^(n - 1) n = 3^n (5 - 2 n)

Multiply -1 and -7 together.
×3^(n - 1) - 2×3^(n - 1) n = 3^n (5 - 2 n)

Distribute 3^n over 5 - 2 n.
3^n (5 - 2 n) = 3^n×5 + 3^n (-2 n):

7×3^(n - 1) - 2×3^(n - 1) n = 5×3^n - 2×3^n n =(5 - 2n)*3^n

 Sep 16, 2018
edited by Guest  Sep 16, 2018
 #4
avatar+27775 
+1

Hmmm!   

 

n        3^(n-1)(n-1)                n3^n

0        3^(-1)(-1) = -1/3         0*3^0 = 0

1        3^(1-1)(1-1) = 0         1*3^1 = 3

2        3^(2-1)(2-1) = 3         2*3^2 = 18

...etc.

Alan  Sep 17, 2018

9 Online Users

avatar